Clinical significance and prognostic value of small nucleolar RNA SNORA38 in breast cancer - Song, Jian; Zheng, Ang; Li, Shan; Zhang, Wenrong; Zhang, Meilin; Li, Xingzhe; Jin, Feng; Ji, Ziyao (Frontiers in Oncology, 2022)
Background: Breast cancer is the most common malignant tumor among women worldwide, and breast cancer stem cells (BCSCs) are believed to be the source of tumorigenesis. New findings suggest that small nucleolar RNAs (snoRNAs) play a significant role in tumor development. Methods: The Cancer Genome Atlas (TCGA) and Kaplan-Meier survival analysis were used to demonstrate expression and survival of SNORA38 signature. In situ hybridization (ISH) and immunohistochemical (IHC) were conducted to analyze the correlation between SNORA38 and stemness biomarker in 77 BC samples. Gene Set Enrichment Analysis (GSEA) was performed to investigate the mechanisms related to SNORA38 expression in BC. Real-time qPCR was employed to evaluate the expression of SNORA38 in breast cancer cell lines. Results: In the public database and patients' biopsies, SNORA38 was significantly upregulated in breast cancer. Furthermore, the expression of SNORA38 was significantly correlated with tumor size, lymph node metastasis, and TNM stage, among which tumor size was an independent factor for SNORA38 expression. Higher SNORA38 expression was associated with shorter overall survival (OS). Meanwhile, SNORA38 was positively associated with the stem cell marker OCT-4, which suggested that SNORA38 might be related to breast cancer stemness. Conclusions: SNORA38 is an important carcinogenic snoRNA in breast cancer and might be a prognostic biomarker for breast cancer.